Antidiabetic medication de‐escalation following bariatric surgery: 减肥手术之后可以降级使用降糖药物. Issue 9 (28th May 2018) - Vouri, Scott M.; Chen, Jiajing; Sparkman, Jayme; Salles, Arghavan; Micek, Scott T.
Abstract : Highlights There is a de‐escalation of antidiabetes medications prescribed following bariatric surgery. Antidiabetes medication utilization following bariatric surgery does not appear to be consistent with clinical practice guidelines.